(untitled) (Ann Arbor, U.S.A., 2008)
Leadership skills are indispensable in language teaching and learning, and the effectiveness of these skills directly affect the quality of language education, the soundness of a program, and the satisfaction level of both teachers and students in the language classrooms and beyond. nbsp; Part 1 of this collection provides the theoretical underpinnings of leadership development.nbsp; Part 2 focuses on leadership skills and strategies on the topics of interpersonal communication, personal organization skills, and program organization skills.nbsp; Part 3 discusses ELT leadership issues in U.S. public schools.
Keywords: English language,Educational leadership,English teachers; Study and teaching,Foreign speakers,Training of